Shear Deformation Analysis of Fabric Prepreg through Picture-Frame Test and Finite Element Method - Chang Lin, Guo; Bo Yuan, Xue; Feng Tan, Hui (Asian Journal of Chemistry, 2014)
Based on picture-frame test and finite element method (FEM), shear behaviour of carbon fabric prepreg, which is made of carbon plain fabric and pre-consolidated epoxy resin, is studied at meso-level. According to the geometrical characteristics of the carbon fabric prepreg, a 3D unit cell model of woven fabric is established and the meso-mechanism of deformation is modelled by FEM. In simulation, the periodic boundary conditions are adopted and the viscous resin is characterized by the friction between yarns. The relationship of shear force and shear angle is obtained by FEM simulation and the results show that shear force increases significantly when shear angle is up to a certain value. The validity of FEM simulation results is verified by a picture-frame test.